Risk Assessment Methods for Power Utility Planning - Hertzmark, Donald (World Bank, Washington, DC, 2014)
This ESMAP report summarizes an expert consultation on electricity system investment planning and modeling held at the World Bank in Washington D.C. on June 27-28, 2006. The workshop brought together practitioners, analysts, regulators and software vendors to discuss the changes in both the external environment affecting the use of simulation models for investment planning and the advances in the art and science of such modeling over the past few years. In addition to the focus on generation investment modeling, a key subject of interest at the workshop was the ability to identify, quantify and, where possible, mitigate risks in power systems investments. The report is organized as follows: introduction to the issues; synopsis of the workshop and summary of discussions; findings and recommendations; and annexes.